2021
DOI: 10.1002/cft2.20083
|View full text |Cite
|
Sign up to set email alerts
|

Annual bluegrass control in bermudagrass using dimethenamid and pendimethalin

Abstract: A 2-yr field experiment was conducted at three locations across Tennessee during 2017-2018 to determine if early-postemergence (EPOST) applications of FreeHand [pendimethalin (3,4-dimethyl-2,6-control annual bluegrass (Poa annua L.)(ABG) similar to Kerb SC [pronamide (3,benzamide)] and 3,]. Across all locations and years, EPOST applications of FreeHand at 200 lb acre -1 controlled ABG by 88 to 100% 23 wk after the initial treatment, more than or equal to Kerb SC and Princep. Follow-up research was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Work by Carroll et al. (2020) determined that early post‐emergence applications of FreeHand (pendimethalin + dimethenamid) could be used in a herbicide program to help prevent the development of herbicide‐resistant annual bluegrass populations. Regarding controlling annual bluegrass with mechanical methods, Carroll, Brosnan, Unruh, et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Work by Carroll et al. (2020) determined that early post‐emergence applications of FreeHand (pendimethalin + dimethenamid) could be used in a herbicide program to help prevent the development of herbicide‐resistant annual bluegrass populations. Regarding controlling annual bluegrass with mechanical methods, Carroll, Brosnan, Unruh, et al.…”
Section: Resultsmentioning
confidence: 99%
“…and McCurdy et al (2023) has identified several instances of annual bluegrass herbicide resistance and provided alternative chemistries. Work byCarroll et al (2020) determined that early post-emergence applications of FreeHand (pendimethalin + dimethenamid) could be used in a herbicide program to help prevent the development of herbicideresistant annual bluegrass populations. Regarding controlling annual bluegrass with mechanical methods,Carroll, Brosnan, Unruh, et al (2021) andBrosnan et al (2020) found that fraise mowing was an effective method at reducing annual bluegrass populations in hybrid bermudagrass [Cynodon dactylon (L.) Pers.…”
mentioning
confidence: 99%
See 1 more Smart Citation